2010
DOI: 10.1097/mop.0b013e32833e2723
|View full text |Cite
|
Sign up to set email alerts
|

Folate protection from congenital heart defects linked with canonical Wnt signaling and epigenetics

Abstract: Purpose of review-Environmental factors, such as drugs, chemicals, or abnormal concentrations of natural metabolites induce birth defects. Environmental effects on cardiogenesis have been little studied in contrast to neurogenesis. This review presents evidence on three environmental factors, alcohol, the drug lithium (Li), and the metabolite homocysteine (HCy), impacting the Wnt/β-catenin pathway during cardiac development and folate (FA) protection.Recent findings-Animal and epidemiological studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…Too low or too high levels of retinoic acid (RA) signaling are known to cause cardiac and other effects very similar to those observed after neural crest ablation (Sinning, ; Zile, ; Pan and Baker, ). Lithium, elevated homocysteine, and ethanol may work through a common pathway, the one carbon cycle, that is rescued by folate and other compounds (Linask and Laties, ; Han et al, ; Linask and Huhta, and reviewed in van Gelder et al, ; Rosenquist, ). This link to a common pathway suggests that an understanding of how one teratogen causes defects may elucidate a general mechanism that might be activated by other teratogens.…”
Section: Teratogens Disturb Neural Crest Cellsmentioning
confidence: 99%
“…Too low or too high levels of retinoic acid (RA) signaling are known to cause cardiac and other effects very similar to those observed after neural crest ablation (Sinning, ; Zile, ; Pan and Baker, ). Lithium, elevated homocysteine, and ethanol may work through a common pathway, the one carbon cycle, that is rescued by folate and other compounds (Linask and Laties, ; Han et al, ; Linask and Huhta, and reviewed in van Gelder et al, ; Rosenquist, ). This link to a common pathway suggests that an understanding of how one teratogen causes defects may elucidate a general mechanism that might be activated by other teratogens.…”
Section: Teratogens Disturb Neural Crest Cellsmentioning
confidence: 99%
“…Our previous observations suggested that EOM from PM2.5 induced heart defects in zebrafish embryos, which could be prevented either by CH223191 (an AhR inhibitor) or by CHIR99021 (a Wnt activator). Since FA has been reported to be involved in the canonical Wnt/β‐catenin pathway to rescue lithium‐induced vertebrate cardiac anomalies, we hypothesized that FA may also prevent PM2.5‐induced heart defects by interfering AhR and Wnt/β‐catenin signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…People who consume low levels of folate or who have low folate concentrations in their blood, have a significantly increased risk of developing CV disease [59], despite the confusion regarding possible lack of value, or even harm, from direct supplementation with folate combined with vitamins B6 and B12 [45]. On the other hand, folate in the early pregnancy of a mother-to-be, in combination with myo-inositol, may favorably modify epigenetics to help prevent environmentally induced birth defects associated with congenital heart disease [73].…”
Section: Nutritional Modification Of Epigeneticsmentioning
confidence: 96%